Do livro ao cinema: memórias da ditadura em Batismo de Sangue e O que é isso, companheiro? - Gomes, Victor Emmanuel Farias (2014)
The present work analyses two films produced in Brazil which has the military dictatorship (1964-1985) as the subject of his narratives. O que é isso, companheiro? (1997), directed by Bruno Barreto, and Batismo de Sangue (2007), by Helvécio Ratton. They are understood as vehicles of construction and appropriation of memories. The research trails the way since the publication of the books that inspired the movies till the movie’s release. Besides the books and movies narrative the essay deals with the personalities who wrote versions about the dictatorial past: moviemakers, armed force militants and writers. In the decades that followed the political freedom the memories about the period of dictatorship are built and reconstructed within the dialogue with the environment of the personalities and the transforming political structures. Through the analysis of the use, meanings and circulation of the cultural industrial products it is possible to have a view of the actual concepts of the dictatorship past and also identify the debates about these memories. The polemics and interpretations that rises from the literary and cinema versions of “O que é isso, companheiro” e “Batismo de Sangue” is used to investigate the process of auto critics of the armed fight, the construction of the emblematic figures of the opposition to the regime, such as Tito de Alencar e Carlos Marighella, the silence about the collaboration and omission before the arbitrary, among other questions that arises from the elaboration about the years of lead.